The History and Development of Posterior Denture TeethÃƒÂ¢Ã¢â€šÂ¬Ã¢â‚¬ÂIntroduction, Part II: Artificial Tooth Development in America Through the Nineteenth Century - Robert L. Engelmeier, DMD, MS (Journal of Prosthodontics, 2003)
PART I of this series of articles traced the development of artificial denture teeth from the late fifteenth century through the early nineteenth century.